Junie B. Jones is Captain Field Day - Park, Barbara; Brunkus, Denise (New York : Random House, 2001)
As captain of Room Nine's field day team, Junie B. Jones tries to rally her troops after they lose several events.
"A Stepping Stone book."
Accelerated Reader
1 3 6 8 9 10 11 12 13 15 17 18 19 20 21 26 27 29 30 33 34 39
Keywords: Winning and losing -- Fiction; Kindergarten -- Fiction; Schools -- Fiction